Quantifying the economic impacts of COVID-19 policy responses on Canada's provinces in (almost) real time - Christopher Cotton; Brett Crowley; Bahman Kashi; Huw Lloyd-Ellis; Frederic Tremblay (Queen's University, Department of Economics, 2020)
We develop a methodology to track and quantify the economic impacts of lock-down and re-opening policies by Canadian provinces in response to the COVID-19 pandemic, using data that is available with a relatively short time-lag. To do so, we adapt, calibrate and implement a dynamic, seasonally-adjusted, input-output model with supply constraints. Our framework allows us to quantify potential scenarios for the impacts of lock-down and reopening which allow for dynamic complementarities between industries, seasonal fluctuations, and changes in the composition of demand. Taking account of the observed variation in re-opening strategies across provinces, we estimate the costs of the policy response in term of lost hours of employment and production.
Keywords: I18; C67; E61; 330; COVID-19; pandemic; lock-down; scenario analysis